Immunosuppressive networks and checkpoints controlling antitumor immunity and their blockade in the development of cancer immunotherapeutics and vaccines. - MILLS, KINGSTON (My University, 2013)
Vaccines that promote protective adaptive immune responses have been successfully developed against a range of infectious diseases, and these are normally administered prior to exposure with the relevant virus or bacteria. Adaptive immunity also plays a critical role in the control of tumors. Immunotherapeutics and vaccines that promote effector T cell responses have the potential to eliminate tumors when used in a therapeutic setting. However, the induction of protective antitumor immunity is compromised by innate immunosuppressive mechanisms and regulatory cells that often dominate the tumor microenvironment. Recent studies have shown that blocking these suppressor cells and immune checkpoints to allow induction of antitumor immunity is a successful immunotherapeutic modality for the treatment of cancer. Furthermore, stimulation of innate and consequently adaptive immune responses with concomitant inhibition of immune suppression, especially that mediated by regulatory T (Treg) cells, is emerging as a promising approach to enhance the efficacy of therapeutic vaccines against cancer. This review describes the immunosuppressive mechanisms controlling antitumor immunity and the novel strategies being employed to design effective immunotherapeutics against tumors based on inhibition of suppressor cells or blockade of immune checkpoints to allow induction of more potent effector T cell responses. This review also discusses the potential of using a combination of adjuvants with inhibition of immune checkpoint or suppressor cells for therapeutic vaccines and the translation of pre-clinical studies to the next-generation vaccines against cancer in humans.Keywords: immunotherapy; vaccine; antitumor immunity; immune checkpoint; regulatory T cell; Toll-like receptor agonist
PUBLISHED
Keywords: Toll-like receptor agonist; regulatory T cell; immune checkpoint; antitumor immunity; Vaccine; immunotherapy; Cancer; Immunology, Inflammation & Infection